2020
DOI: 10.3389/fpsyt.2020.00055
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for Obsessive–Compulsive Disorder: A Long Term Naturalistic Follow Up Study in a Single Institution

Abstract: Introduction: Deep brain stimulation (DBS) is a proven, effective tool in the treatment of movement disorders. Expansion of indications for DBS into the realm of neuropsychiatric disorders, especially obsessive-compulsive disorder (OCD), has gained fervent interest, although data on appropriate clinical utilization remains limited. Methods: A retrospective, naturalistic study followed nine severely affected OCD patients (average YBOCs score before implantation 34.2 ± 2.5) treated with DBS of ventral capsule/ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 79 publications
0
22
0
1
Order By: Relevance
“…We found that freezing levels in mice that received DBS in the dDG during fear extinction were significantly lower than in mice from the sham group; DBS may help to suppress fear expression during fear extinction training. Although DBS has been used routinely to treat depression 47 and obsessivecompulsive disorder 48 and preclinical DBS studies in fear conditioning animal models have suggested its potential use for treatment-resistant PTSD, [49][50][51] very few studies have explored the clinical effect of DBS in PTSD. [52][53][54] About 20% to 30% of PTSD patients do not respond to medications and conventional psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We found that freezing levels in mice that received DBS in the dDG during fear extinction were significantly lower than in mice from the sham group; DBS may help to suppress fear expression during fear extinction training. Although DBS has been used routinely to treat depression 47 and obsessivecompulsive disorder 48 and preclinical DBS studies in fear conditioning animal models have suggested its potential use for treatment-resistant PTSD, [49][50][51] very few studies have explored the clinical effect of DBS in PTSD. [52][53][54] About 20% to 30% of PTSD patients do not respond to medications and conventional psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…DBS is the most prevalent example of symptomatic interventions in movement disorders and other neurological and psychiatric conditions (McKinnon et al, 2019 , Sullivan et al, 2021 ). Recent developments of long-lasting and rechargeable battery to power implantable pulse generator (IPG) and precise segmental electrodes can improve patient comfort (Holland et al, 2020 ) and enable on-demand delivery of stimulation based on closed-loop designs (Bouthour et al, 2019 ). Stimulation of neuroanatomic targets in central and peripheral nerve systems is believed to modulate neuronal activity locally and remotely in order to restore circuitry involved in normal brain functioning.…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…Firstly, IPG had limited battery lives and had to be replaced surgically and reprogrammed after about 5 years. This drawback was mitigated by the development of rechargeable implantable pulse generators to increase patient comfort, reduce long-term cost for DBS and eliminate the surgery for IPG placement (De Vloo et al, 2018 , Hitti et al, 2018 , Holland et al, 2020 ). Secondly, the efficacy of this intervention had been variable depending on accurate placement of electrodes on specific targets and precise setting of stimulation paradigms for each individual patient with a particular disorder.…”
Section: Development Of New Frontiersmentioning
confidence: 99%
“…Challenges in optimizing invasive neuromodulation are not unique to depression. Studies of DBS for obsessive-compulsive disorder (OCD) have varied on probe placement and treatment response rates (21)(22)(23)(24). Furthermore, methods for predicting individual likelihood of response are limited.…”
Section: Current Treatmentmentioning
confidence: 99%